Marketing analysis of catfish (Clarias batrachus) in Lingkungan Marusu, Maros Regency - Lukman Daris; Ade Fitrah Maharini; Alpiani Alpiani; Febri Febri (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
The role of aquaculture is vast in efforts to increase the quality and quantity of fishery products and to meet the nutritional food needs of the people of the Maros and South Sulawesi Regencies. Catfish is one of the fisheries commodities that has good prospects for development. This is supported by the characteristics of catfish, which have high nutritional content, fast growth, are easy to breed, and can be maintained in almost all aquaculture containers. This study examines the flow of catfish marketing and analyses the differences in catfish prices in the Marusu Village, Palantikan Village, Maros Baru District, and Maros Regency. The research method was interviews assisted with a questionnaire instrument. The analysis used in this study is descriptive qualitative analysis for marketing channels and farmer's share analysis to measure the efficiency of acceptance of marketing channels for seed and catfish cultivators. The marketing channel for catfish seeds in the Marusu environment consists of 2 channels. Channel 1 starts from cultivators, collectors within the Marusu environment, and outside collectors and ends with cultivators outside the Maros area (consumers), channel 2 starts from cultivators, collectors and cultivators outside the Maros Regency area (consumers). The catfish marketing channel also consists of 2 channels. Channel 1, namely, starts with cultivators, retailers and consumers. Channel 2 is the cultivator directly to the consumer. For catfish fingerlings, farmers in marketing channels 1 and 2 are 75%, respectively. In contrast, the farmer's share in marketing channels 1 and 2 for catfish is 66.67% and 100%.